Always faithful, always forward the forging of a Special Operations Marine - Couch, Dick (Berkley Caliber, 2014)
Always Faithful, Always Forward follows the journey of a class of Marine candidates from their recruitment, through assessment and selection, to their qualification as Marines Special Operators. The assessment, selection, and training regimes are a combination of psychological testing and intense military training as well as being a physical and professional rite of passage. MARSOC Marines must be efficient, agile,